Transcriptome-Based Molecular Networks Uncovered Interplay Between Druggable Genes of CD8+ T Cells and Changes in Immune Cell Landscape in Patients With Pulmonary Tuberculosis - Alsulaimany, Faten Ahmad; Zabermawi, Nidal M. Omer; Almukadi, Haifa; Parambath, Snijesh V.; Shetty, Preetha Jayasheela; Vaidyanathan, Venkatesh; Elango, Ramu; Babanaganapalli, Babajan; Shaik, Noor Ahmad (Frontiers in Medicine, 2022)
BACKGROUND: Tuberculosis (TB) is a major infectious disease, where incomplete information about host genetics and immune responses is hindering the development of transformative therapies. This study characterized the immune cell landscape and blood transcriptomic profile of pulmonary TB (PTB) patients to identify the potential therapeutic biomarkers. METHODS: The blood transcriptome profile of PTB patients and controls was used for fractionating immune cell populations with the CIBERSORT algorithm and then to identify differentially expressed genes (DEGs) with R/Bioconductor packages. Later, systems biology investigations (like semantic similarity, gene correlation, and graph theory parameters) were implemented to prioritize druggable genes contributing to the immune cell alterations in TB patients. Finally, RT-PCR was used to confirm gene expression levels. RESULTS: PTB patients had higher levels of four immune subpopulations like CD8+T cells (p=1.9×10-8), NK cells resting (p=6.3×10-5), monocytes (p=6.4×10-6) and neutrophils (p=1.6×10-7). The functional enrichment of 624 DEGs identified in PTB patient blood transcriptome revealed the major dysregulation of T cell related ontologies and pathways (q ≤0.05). Of the 96 DEGs shared between transcriptome and immune cell types, 39 overlapped with TB meta-profiling genetic signatures, and their semantic similarity analysis with remaining 57 genes, yielded 45 new candidate TB markers. This study identified 9 CD8+T cell associated genes (ITK, CD2, CD6, CD247, ZAP70, CD3D, SH2D1A, CD3E, and IL7R) as potential therapeutic targets of PTB by combining computational druggability and co-expression (r2 >=|0.7|) approaches. CONCLUSION: The changes in immune cell proportion, and the down regulation of T cell related genes may provide new insight in developing therapeutic compounds against chronic tuberculosis.